+0

+1
249
1

(2x2)-4

Jan 9, 2018
edited by Guest  Jan 9, 2018

#1
+2340
+2

Let's use the exponent rules to simplify this expression.

$$\left(2x^2\right)^{-4}=2^{-4}\left(x^2\right)^{-4}$$ by the power of a product exponent rule.

$$2^{-4}\left(x^2\right)^{-4}=2^{-4}x^{-8}$$   by the power of a power exponent rule.

$$2^{-4}x^{-8}=\frac{1}{2^4x^8}$$               by the negative power exponent rule.

$$\frac{1}{2^4x^8}=\frac{1}{16x^8}$$                     This step does not involve an exponent rule but rather this is just simplification.

Jan 9, 2018

#1
+2340
+2

Let's use the exponent rules to simplify this expression.

$$\left(2x^2\right)^{-4}=2^{-4}\left(x^2\right)^{-4}$$ by the power of a product exponent rule.

$$2^{-4}\left(x^2\right)^{-4}=2^{-4}x^{-8}$$   by the power of a power exponent rule.

$$2^{-4}x^{-8}=\frac{1}{2^4x^8}$$               by the negative power exponent rule.

$$\frac{1}{2^4x^8}=\frac{1}{16x^8}$$                     This step does not involve an exponent rule but rather this is just simplification.

TheXSquaredFactor Jan 9, 2018